27 years of experience with the comprehensive surgical treatment of prune belly syndrome. Issue 5 (October 2015) - Lopes, R.I.; Tavares, A.; Srougi, M.; Dénes, F.T.
Summary: Introduction: Prune belly syndrome (PBS) presents with three main features: abdominal wall flaccidity, urological abnormalities and cryptorchidism. As a result, urologists must consider the eventual repair of the abdominal wall flaccidity and urinary tract abnormalities, and the mandatory correction of cryptorchidism, as well as decide whether to perform the procedures in a single comprehensive approach or in multiple steps. Objectives: To report experiences with comprehensive surgical management of prune belly syndrome. Material and methods: From 1987 to 2014, 46 children with PBS were submitted for comprehensive surgical treatment. According to individual needs, treatment aimed to correct the abdominal flaccidity, reconstruct the urinary tract, and perform bilateral orchiopexy and circumcision, which were performed in one procedure. Urinary tract reconstruction was indicated whenever pyelo-ureteral dilatation with evidence of significant stasis and/or vesicoureteral reflux was associated with recurrent urinary tract infections (UTI). Treatment for this cohort included: 44 abdominoplasties, 40 upper urinary tract reconstructions, 44 cystoplasties associated with three appendico-vesicostomies, 46 bilateral orchiopexies and 36 circumcisions. The median age at surgery was 16 months and children were followed for a median of 143 months. Results: Abdominal appearance and tonus were improved in 90% of the children after the primary surgery and 100% after reoperation. Upper urinary tract reconstruction was performed in most children and long-term follow-up showed functional stabilization of the urinary tract in about 90% of the children, with progression to renal failure in 10%. Lower urinary tract reconstruction was performed in most children (95.6%); on late follow-up, continence was observed in 81% of them, while incontinence was present in 19% and usually associated with polyuria. Adequate bladder emptying was possible in most boys (82.6%), while the remaining required clean intermittent catheterization. Pre-operative UTI was present in 89.1% and urinary sepsis in 15.2%. Postoperatively, the incidence of laboratorial UTI was significantly reduced to 39.1%, while urinary sepsis was absent. Bilateral orchiopexy was performed in all children, with 85% of the testes becoming normal in size and well located in the scrotum. Conclusions: Comprehensive surgical treatment is feasible and has good long-term results. A considerable incidence of reoperations due to complications or progression of the disease was observed. The long-term results for reno-ureteral anatomy and function, bladder function, infection, testicular size and location, as well as abdominal aspect and tonus, show that comprehensive surgery is an adequate method for managing children with PBS.